Gut microbiota and obesity: New insights - Sarmiento-Andrade, Yoredy; Suárez, Rosario; Quintero, Beatriz; Garrochamba, Kleber; Chapela, Sebastián Pablo (Frontiers in Nutrition, 2022)
Obesity is a pathology whose incidence is increasing throughout the world. There are many pathologies associated with obesity. In recent years, the influence of the microbiota on both health and pathological states has been known. There is growing information related to changes in the microbiome and obesity, as well as its associated pathologies. Changes associated with age, exercise, and weight changes have been described. In addition, metabolic changes associated with the microbiota, bariatric surgery and fecal matter transplantation are described. In this review, we summarize the biology and physiology of microbiota in obese patients, its role in the pathophysiology of several disorders associated, and the emerging therapeutic applications of prebiotics, probiotics, and fecal microbiota transplantation.